2013
DOI: 10.1002/acr.22144
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Metabolic Syndrome and Carotid Intima‐Media Thickness: Cross‐Sectional Comparison Between Psoriasis and Psoriatic Arthritis

Abstract: Objective. To determine the differences in carotid intima-media thickness (CIMT) between patients with psoriatic diseases with and without metabolic syndrome. Methods. Eligible patients from the Cardiometabolic Outcome Measures in Psoriatic Arthritis Study database, which is comprised of both psoriasis and psoriatic arthritis (PsA) patients enrolled at 2 academic medical centers, were included. Detailed cardiovascular (CV) risk factors, including metabolic syndrome profiles, medication use, disease activity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 24 publications
4
33
0
1
Order By: Relevance
“…Another study conducted in a large cohort of psoriatic patients have underlined that the risk of CV mortality was 50% higher compared to the general population [42] . These data were confirmed by Lin et al [43] , who detected that patients affected by psoriatic arthritis (PsA) had an increased prevalence of metabolic syndrome with significantly greater carotid intimamedia thickness compared to patients with psoriasis only. Furthermore, greatest CIMT measurements were detectable in PsA patients with metabolic syndrome compared to PsA patients without metabolic syndrome and psoriasis patients with or without metabolic syndrome [43] .…”
Section: Psoriasis and Prothrombotic Statesupporting
confidence: 76%
“…Another study conducted in a large cohort of psoriatic patients have underlined that the risk of CV mortality was 50% higher compared to the general population [42] . These data were confirmed by Lin et al [43] , who detected that patients affected by psoriatic arthritis (PsA) had an increased prevalence of metabolic syndrome with significantly greater carotid intimamedia thickness compared to patients with psoriasis only. Furthermore, greatest CIMT measurements were detectable in PsA patients with metabolic syndrome compared to PsA patients without metabolic syndrome and psoriasis patients with or without metabolic syndrome [43] .…”
Section: Psoriasis and Prothrombotic Statesupporting
confidence: 76%
“…Among individuals with PsA, a significant correlation between serum uric acid levels and subclinical atherosclerosis was found as indicated by increased carotid intima-medial thickness 37 38 45. Onat et al 46 showed that elevated uric acid levels correlate with a pro-inflammatory state and high-density lipoprotein dysfunction and that risk of coronary heart disease is independently predicted by elevated uric acid levels in non-diabetic men, modulated by the metabolic syndrome and gender.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, among patients without PsA, the prevalence of MetS was comparable to an estimated prevalence of MetS in the Western population of 15-24% 7,8 . There are now emerging data investigating the association of burden of inflammation in PsA with comorbidities 9,10 . For example, a recent study has shown that the cumulative inflammatory burden, as reflected by cumulative averages of repeated measures of erythrocyte sedimentation rate, was associated with increased arterial stiffness in patients with PsA, even after adjustment for CV risk factors, emphasizing the important involvement of chronic inflammation in accelerating the development of CVD in patients with PsA 9 .…”
Section: To the Editormentioning
confidence: 99%